Utilization of aquatic weeds fibers for handmade papermaking - Emmclan, Lau Sheng Hann; Zakaria @ Ya, Muta Harah; Bujang, Japar Sidik (North Carolina State University, 2018)
Increasing global paper consumption has fostered the search for new alternative non-wood fiber sources. The aquatic weeds Cyperus digitatus, Cyperus iria, and Scirpus grossus were analysed for their fiber characteristics and chemical composition, and the processed fibers were transformed into handmade paper. The selected species yielded medium-length fibers (0.92 mm to 1.03 mm), which were thin-walled with a lumen diameter (3.37 µm to 5.26 µm) wider than cell wall thickness (2.73 µm to 2.97 µm). In terms of fiber derived values, the selected species possessed a slenderness ratio of 86.5 to 113.1 (favourable, > 30) and flexibility coefficient of 35.2 to 47.6 (favourable, within the range 50 to 70), which was classified as rigid fiber. The species also contained high cellulose, 42.1% to 44.8% (favourable, > 40%) and hemicellulose content, 42.8% to 45.6% (favourable, within the range of 30% to 50%), and low lignin content, 10.6% to 11.8% (favourable, < 12%). Handmade paper of Cyperus digitatus possessed relatively high tensile strength (2.61 ± 0.15 kN/m) and breaking length (1.20 ± 0.07 km) among studied species. Comparison with other non-wood fibers indicated that the studied plants fibers can be used for production of paper plates, paperboard, and decorative paper.